Comparative Study of Soxhlet Extraction and Hydraulic Pressing for Biokerosene Production from Rubber Seeds (Hevea brasiliensis) - Indah Retno Wulandary; Abubakar Tuhuloula; Meilana Dharma Putra; Dewi Dheana Herman; Anisa Maghfirah; Marliana Hartania; Nur Ainah (Eksergi, 2026)
Biokerosene is a renewable alternative to fossil-based kerosene, derived from biological resources such as rubber seeds. This study evaluates the effects of Soxhlet extraction and hydraulic pressing on biokerosene production, including the influence of stirring speed during degumming and the physicochemical characteristics of the product. Rubber seed masses of 50, 75, and 100 g were tested, with degumming conducted at 150 and 300 rpm. The highest oil yield (46%) was obtained using Soxhlet extraction at 50 g. However, superior product quality was achieved through hydraulic pressing at 75 g and 150 rpm, yielding the lowest free fatty acid (FFA) value (4.47 mg KOH/g) and the highest proportion of C10–C16 hydrocarbons (56.54%). The resulting biokerosene exhibited densities of 913.8–929.4 kg/m³ and viscosities of 2.6–3.6 cSt. These findings indicate that Soxhlet extraction is more effective for maximizing yield, while hydraulic pressing produces higher quality intermediates that are better suited for downstream upgrading into aviation fuel.